Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Les usages de la sexualité chez Foucault - PROBYN, Elspeth (Sociologie et sociétés, 1997)
Cet article expose de façon schématique comment certains aspects de la pensée de Foucault dépassent les deux pôles qui ont défini la plupart des débats dans le champ des études gaies et lesbiennes à propos de la sexualité
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Sexy bodies: the strange carnalities of feminism - Grosz, E. A.; Probyn, Elspeth (Routledge, 1995)
Are bodies sexy? How? In what sorts of ways? Sexy Bodies investigates the production of sexual bodies and sexual practices, of sexualities which are dyke, bi, transracial, and even hetero. It celebrates lesbian and queer sexualities but also explores what runs underneath and within all sexualities, discovering what is fundamentally weird and strange about all bodies, all carnalities. Looking at a pleasurable variety of cultural forms and texts, the contributors consider the particular charms of girls and horses, from National Velvet to Marnie; discuss figures of the lesbian body from vampires to tribades to tomboys; uncover 'virtual' lesbians in the fiction of Jeanette Winterson; track desire in the music of legendary Blues singers; and investigate the ever-scrutinised and celebrated body of Elizabeth Taylor. The collection includes two important pieces of fiction by Mary Fallon and Nicole Brossard. Sexy Bodies makes new connections between and amongst bodies, cruising the borders of the obscene, the pleasurable, the desirable and the hitherto unspoken rethinking sexuality anew as deeply and strangely sexy.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; féminisme pop; identités LGBTQIA2+; lesbianisme; lit4700; premier cycle; queer; ressource en ligne; sexualité; thématiques